The Pharmacology and Clinical Efficacy of Antiseizure Medications: From Bromide Salts to Cenobamate and Beyond - Löscher, Wolfgang; Klein, Pavel (CNS drugs, 2021)
Epilepsy is one of the most common and disabling chronic neurological disorders. Antiseizure medications (ASMs), previously referred to as anticonvulsant or antiepileptic drugs, are the mainstay of symptomatic epilepsy treatment. Epilepsy is a multifaceted complex disease and so is its treatment. Currently, about 30 ASMs are available for epilepsy therapy. Furthermore, several ASMs are approved therapies in nonepileptic conditions, including neuropathic pain, migraine, bipolar disorder, and generalized anxiety disorder. Because of this wide spectrum of therapeutic activity, ASMs are among the most often prescribed centrally active agents. Most ASMs act by modulation of voltage-gated ion channels; by enhancement of gamma aminobutyric acid-mediated inhibition; through interactions with elements of the synaptic release machinery; by blockade of ionotropic glutamate receptors; or by combinations of these mechanisms. Because of differences in their mechanisms of action, most ASMs do not suppress all types of seizures, so appropriate treatment choices are important. The goal of epilepsy therapy is the complete elimination of seizures; however, this is not achievable in about one-third of patients. Both in vivo and in vitro models of seizures and epilepsy are used to discover ASMs that are more effective in patients with continued drug-resistant seizures. Furthermore, therapies that are specific to epilepsy etiology are being developed. Currently, ~ 30 new compounds with diverse antiseizure mechanisms are in the preclinical or clinical drug development pipeline. Moreover, therapies with potential antiepileptogenic or disease-modifying effects are in preclinical and clinical development. Overall, the world of epilepsy therapy development is changing and evolving in many exciting and important ways. However, while new epilepsy therapies are developed, knowledge of the pharmacokinetics, antiseizure efficacy and spectrum, and adverse effect profiles of currently used ASMs is an essential component of treating epilepsy successfully and maintaining a high quality of life for every patient, particularly those receiving polypharmacy for drug-resistant seizures.